Antioxidative, Thrombolytic and Cytotoxic Potentials of Jatropha pandurifolia Stem bark and Syzygium reticulatum Leaf (Dhaka University Journal of Pharmaceutical Sciences, 2023)
The study attempted to illustrate the antioxidant, thrombolytic and cytotoxic properties of two different medicinal plants, Jatropha pandurifolia and Syzygium reticulatum. In vitro antioxidative activity was tested through qualitative and quantitative DPPH scavenging assay which revealed the radical scavenging activity. Methanolic stem bark extract of Jatropha pandurifolia (MSJP) and ethyl acetate leaf extract of Syzygium reticulatum (EALSR) showed moderate clot rupture activity, the value of which were 61.30 ± 2.35% (**P